2012
DOI: 10.1016/j.thromres.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a multivariate model to predict mortality from pulmonary embolism with cancer: The POMPE-C tool

Abstract: Background Clinical guidelines recommend risk stratification of patients with acute pulmonary embolism (PE). Active cancer increases risk of PE and worsens prognosis, but also causes incidental PE that may be discovered during cancer staging. No quantitative decision instrument has been derived specifically for patients with active cancer and PE. Methods Classification and regression technique was used to reduce 25 variables prospectively collected from 408 patients with AC and PE. Selected variables were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
74
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 34 publications
2
74
1
1
Order By: Relevance
“…4) Beyond symptoms, the presence of abnormal vital signs (such as systolic blood pressure <100 mmHg, heart rate >100 beats per minute and oxygen saturation <95%) predicted an increased risk of short-term mortality. Previous studies have arrived at the same conclusion [7,8], suggesting that these clinical signs are the "red flags" to watch out for when managing a patient with cancer-associated PE.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…4) Beyond symptoms, the presence of abnormal vital signs (such as systolic blood pressure <100 mmHg, heart rate >100 beats per minute and oxygen saturation <95%) predicted an increased risk of short-term mortality. Previous studies have arrived at the same conclusion [7,8], suggesting that these clinical signs are the "red flags" to watch out for when managing a patient with cancer-associated PE.…”
mentioning
confidence: 77%
“…Third, the advantage of a three-group classification is unclear to us when the authors actually clearly showed that only the TA-UPE group had its distinct (low) mortality profile. This criticism, however, should not conceal that the current study is, among other previous work on this issue [7,8,22], a stringent attempt to classify cancer-associated PE. Regarding antithrombotic therapy, two end-points are of interest, namely recurrent VTE and major bleeding [9].…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…8 Patients with active malignancy were further risk stratified using the POMPE-C tool (Table 2). 12 Clinicians completed a survey (REDCap; see Data Supplement S1, available as supporting information in the online version of this paper) in real time that required all components of Hestia to be satisfied and initiated a standardized order set including complete blood count, a basic metabolic panel, optionally 1 mg/ kg enoxaparin, and one 15-mg rivaroxaban dose by mouth, prior to discharge. We had two reasons for administering the single dose of enoxaparin in addition to rivaroxaban at diagnosis.…”
Section: Study Protocolmentioning
confidence: 99%
“…While DVT has been treated as an outpatient for many years, recently developed risk stratification tools have been validated to select patients with PE who have a low risk of shortterm complications. [1][2][3][4][5][6][7] In particular, the Hestia criteria identifies a subgroup of PE patients who have a 1.0% mortality rate as outpatients over 3 months and a low rate of short-term complications requiring rehospitalization. 8 In this article, we assumed that many patients with DVT have undiagnosed PE and therefore must undergo the same risk stratification as patients with documented PE.…”
mentioning
confidence: 99%